Neuroendocrine and metabolic responses of Pacific whiteleg shrimp Penaeus vannamei exposed to hypoxia stress - Aparicio-Simón,Benjamín (Pontificia Universidad Católica de Valparaíso. Facultad de Recursos Naturales. Escuela de Ciencias del Mar, 2018)
ABSTRACT Neuroendocrine mechanisms involved in crustacean stress response are different and less understood than those of vertebrates. Although indirect evidence suggests the participation of catecholamines (CA), few studies have analyzed their levels during stress response in crustaceans. This study examined CA levels in hemolymph and tissue of whiteleg shrimp Penaeus vannamei besides other biochemical indicators in response to hypoxia (0.8-1.0 mg L-1). Shrimp were stressed by hypoxia exposure, and their responses were analyzed at several intervals (10-480 min). Hemolymph glucose levels decreased gradually due to a higher demand not compensated by the gluconeogenesis process from hepatopancreas or muscle after 10 min. Lactate levels in hemolymph showed a 5-fold increase after 10 min, and a correlation with CA levels in hemolymph was observed suggesting its possible role in signaling catecholaminergic activation from eyestalk in a period from 10 to 120 min. Protein levels in muscle and hepatopancreas increased gradually throughout the trial indicating the possible use of another energetic substrate as arginine phosphate. A decrease in triacylglyceride levels denotes its preferential utilization as an immediate energy source in the scape response during the first minutes of hypoxia exposure. Heart adrenaline and noradrenaline levels increased rapidly at the beginning of the trial showing a correlation with the use of triacylglycerides and carbohydrates in hepatopancreas and muscle (r = 0.89 and r = 0.93, P < 0.05, respectively). This manuscript reports evidence of CA participation in response to stress due to hypoxia and discusses possible adaptation mechanisms.